Redescription of Neelus fimbriatus Bretfeld & Trinklein, 2000 (Collembola: Neelidae) from Colombia - Marín, Elida P.; Palacios-Vargas, José G. (Zootaxa, 2018)
Neelus fimbriatus is redescribed using specimens from Colombia. Drawings and phase contrast microscope photos of the species are used. New characters are used as tibiotarsal tuberculate setae and abdominal ventral acetabula.